Hyperbolic boundary value problem for semibounded piecewise-homogeneous hollow cylinder - Gromyk, А.; Konet, I.; Pylypiuk, T. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2018)
By means of the method of integral and hybrid integral transforms, in combination with the method of main solutions (influence matrices and Green matrices) the integral image of exact analytical solution of hyperbolic boundary value problem of mathematical physics for semibounded piecewise-homogeneous hollow cylinder is obtained for the first time. Методом інтегральних і гібридних інтегральних перетворень у поєднанні з методом головних розв’язків (матриць впливу та матриць Гріна) вперше побудовано інтегральне зображення точного аналітичного розв’язку гіперболічної крайової задачі математичної фізики для напівобмеженого кусково-однорідного порожнистого циліндра.